Impact of Revascularization Completeness on Outcomes of Patients with Coronary Artery Disease Undergoing Transcatheter Aortic Valve Replacement. Issue 5 (3rd September 2019) - Landt, Martin; Abdelghani, Mohammad; Hemetsberger, Rayyan; Mankerious, Nader; Allali, Abdelhakim; Toelg, Ralph; Richardt, Gert; Abdel-Wahab, Mohamed
ABSTRACT: Background: Coronary artery disease (CAD) is common in aortic stenosis patients, but its proper management in the setting of transcatheter aortic valve replacement (TAVR) is not established. We sought to explore whether the extent of revascularization by percutaneous coronary intervention (PCI) has an impact on clinical outcomes after TAVR. Methods: Out of 875 consecutive patients, 303 underwent PCI prior to TAVR. Baseline (pre-PCI) and residual (post-PCI) SYNTAX score (bSS and rSS), as well as their ratio (SYNTAX revascularization index, SRI) were calculated for 207 patients who underwent PCI for native CAD at a median of four days before TAVR. The endpoints were the 30-day safety endpoint (VARC-2 definition) and 1-year mortality. Results: In patients undergoing PCI prior to TAVR, bSS was 11.0 ± 7.2, rSS was 2.8 ± 5.3, and SRI was 81.7 ± 27.9%. Complete revascularization (rSS = 0 and SRI = 100%) was achieved in 129 patients (62.3%). The rate of the 30-day safety endpoint was influenced by the STS score and the bSS, but not by the completeness of coronary revascularization. At one year post-TAVR, complete revascularization was associated with a lower mortality (adjusted HR, 0.450 [0.218–0.926], p = 0.030). This mortality advantage was more evident in patients with multivessel CAD (n = 130; HR, 0.304 [0.120–0.772]) than in patients with single-vessel CAD (n = 77; HR, 0.752 [0.207–2.731]). Conclusions: In patients with CAD undergoing TAVR, complete percutaneous coronary revascularization is safe and associated with lower one-year mortality, especially in patients with multivessel CAD.